Silicon: Potential to Promote Direct and Indirect Effects on Plant Defense Against Arthropod Pests in Agriculture - Reynolds, Olivia L.; Padula, Matthew P.; Zeng, Rensen; Gurr, Geoff M. (Frontiers in Plant Science, 2016)
Silicon has generally not been considered essential for plant growth, although it is well recognised that many plants, particularly Poacea, have substantial plant tissue concentrations of this element. Recently, however, the International Plant Nutrition Institute, Georgia, USA has listed it as a “beneficial substance”. This reflects the fact that numerous studies have now established that silicon may alleviate both biotic and abiotic stress. This paper explores existing knowledge and recent advances in elucidating the role of silicon in plant defence against biotic stress, particularly against arthropod pests in agriculture and attraction of beneficial insects. Silicon confers resistance to herbivory via two described mechanisms, physical and biochemical/molecular. Until recently, studies have mainly centered on two trophic levels, the herbivore and plant. However, several studies now describe tri-trophic effects involving silicon that operate by attracting predators or parasitoids to plants under herbivore attack. Indeed, it has been demonstrated that silicon-treated, arthropod attacked plants display increased attractiveness to natural enemies, an effect that was reflected in elevated biological control in the field. The reported relationship between soluble silicon and the jasmonic acid (JA) defence pathway and JA and herbivore induced plant volatiles (HIPVs) suggest that soluble silicon may enhance the production of HIPVs. Further, it is feasible that silicon uptake may affect protein expression (or modify proteins structurally) so that they can produce additional, or modify, the HIPV profile of plants. Ultimately, understanding silicon under plant ecological, physiological, biochemical and molecular contexts will assist in fully elucidating the mechanisms behind silicon and plant response to biotic stress at both the bi- and tri-trophic levels.